Agent-Based Music Live Coding: Sonic adventures in 2D. - Roma, Gerard (Organised Sound, 2023)
This article describes agent-based music live coding, an approach for music performance and composition based on programming a set of agents in a 2D plane. This style of programming draws from the tradition of agent-based models and facilitates interactive algorithmic control of data-driven sound synthesis methods such as wave terrain synthesis or corpus-based concatenative synthesis. The main elements are a 'terrain', which may be used to access different types of data, a set of agents and their trajectories, and a set of synthesis functions associated to agents. An implementation using the SuperCollider language is demonstrated.